2017
DOI: 10.15298/rusjtheriol.16.2.01
|View full text |Cite
|
Sign up to set email alerts
|

The first record of Episoriculus umbrinus from Vietnam, with notes on the taxonomic composition of Episoriculus (Mammalia, Soricidae)

Abstract: ABSTRACT. The mitochondrial cytochrome b and nuclear ApoB and RAG2 genes were used to estimate the phylogenetic relationships in Asiatic red-toothed shrews (Soricidae, Episoriculus). Based on molecular data, the genus Episoriculus seems to consist of at least seven valid species: E. baileyi, E. caudatus, E. leucops, E. macrurus, E. sacratus, E. soluensis, and E. umbrinus. Genetic distances among all of them are found to be of 8-16%, with the only low distance (3.4%) being that between E. baileyi and E. leucops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Next, Abramov et al . [2] promoted E. soluensis as an independent species, which was a synonym of E. caudatus . And the type locality of E. soluensis is Pokhara, Nepal in the southern Himalayas (Abramov).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, Abramov et al . [2] promoted E. soluensis as an independent species, which was a synonym of E. caudatus . And the type locality of E. soluensis is Pokhara, Nepal in the southern Himalayas (Abramov).…”
Section: Discussionmentioning
confidence: 99%
“…Hoffmann [7], Motokawa and Lin [13] pointed out that P. fumidus has a unique morphology. Abramov et al [2] erected the new genus Pseudosoriculus for the species. Our analysis also supported new classification status of Pseudosoriculus, and confirmed that P. fumidus does not belong to genus Episoriculus.…”
Section: Species Of Episoriculusmentioning
confidence: 99%
See 1 more Smart Citation
“…We sequenced the complete mitochondrial cytochrome b ( cytb ) gene and fragments of four nuclear loci: apolipoprotein B ( ApoB ), exon 11 of the breast cancer type 1 susceptibility protein ( BRCA1 ), recombination activating gene 2 ( RAG2 ), and the interphotoreceptor retinoid binding photoreceptor ( IRBP ). Primers and polymerase chain reaction protocols for nuclear loci ( ApoB , BRCA1 , IRBP and RAG2 ) are described in Abramov et al (2017a) and Bannikova et al (2018). New primers were designed specifically for amplification and sequencing the complete cytb gene and its short fragments from the historical museum specimen, the holotype of B. griselda (Suppl.…”
Section: Methodsmentioning
confidence: 99%
“…We sequenced the complete mitochondrial cytochrome b ( cytb ) gene and fragments of six nuclear loci: apolipoprotein B ( ApoB ), exon 11 of the breast cancer type 1 susceptibility protein ( BRCA1 ), breast cancer type 2 susceptibility protein ( BRCA2 ), recombination activating gene 2 ( RAG2 ), the interphotoreceptor retinoid‐binding photoreceptor ( IRBP ) and exon 10 of the growth hormone receptor ( GHR ). Primers and polymerase chain reaction protocols for four loci ( ApoB , BRCA1 , IRBP and RAG2 ) are described in Bannikova and Lebedev () and Abramov, Bannikova, Chernetskaya, Lebedev, and Rozhnov (); new protocols and primers for these and other loci are detailed in Supporting Information Table . General methods of cytb extraction, amplification and sequencing follow Bannikova et al.…”
Section: Methodsmentioning
confidence: 99%